Presence of Leptospira sp. and leptospirosis risk factor analysis in Boyolali district, Indonesia - Yuliani Setyaningsih; Apoina Kartini; Nurdin Bahtiar; Apoina Kartini; Siti Fatimah Pradigdo; Lintang Saraswati (SAGE Publishing, 2022)
Background: Leptospirosis is a health problem that causes death in Indonesia. In 2017, Boyolali District was reported that the number of leptospirosis cases reached 40.62 per 100,000 population with a CFR of 23.52%. The determination of risk factors and Leptospira bacteria's presence in the body of water plays an essential role in the transmission of leptospirosis. Design and methods: This study aims to determine the risk factors and Leptospira bacteria's presence in water bodies in Boyolali District. This research is descriptive research with a survey method using a cross-sectional design and an analytical study using an observational method with a case-control approach. The sample was 100 water samples from wells, rivers, and paddy fields in endemic and non-endemic areas of leptospirosis. This study's population was 34 people with leptospirosis in Boyolali Regency in January 2017 - August 2018. Results: There was a significant relationship between leptospirosis incidence in the Boyolali Regency with garbage, the pet presence, a history of injuries, and field activity. Leptospira bacteria are found in rivers (18.18%) and rice fields (6.67%), while in sub-districts with cases occur almost every year. Leptospira are found in wells (18.18%) and rice fields (6.67%). Conclusions: People should pay more attention to home sanitation and the surrounding environment to avoid leptospirosis.